Leadership Style Moderates the Effect of Work Motivation on Teacher Performance at State Junior High Schools in Masohi District - Rudolf Kempa; Irawanto Irawanto; J.E. Lekatompessy (International Journal of Education, Information Technology, and Others, 2022)
The indicators of education quality cannot be separated from the roles of school principals and teachers. As managers and leaders, the principal can organize all components to achieve the expected goals. The use of leadership styles that are appropriate to the work environment will have an impact on the performance of teachers and education personnel. Improving the quality of teacher performance cannot be separated from the urge to plan and implement learning programs properly for the benefit of students. This encouragement shows that there is work motivation that is important for teachers as an indicator of their love for their profession. This study aims to determine (1) the effect of job motivation on teacher performance at State Junior High Schools in Masohi City District and (2) principal leadership style as a variable that moderates the effect of job motivation on teacher performance. The results of the descriptive analysis show that the job motivation of teachers at State Junior High Schools in Masohi City District is in the good category with mean score are 82.88, the leadership style of the principal with mean score 94.45 and teacher performance is also in the category with mean score 127.36. The results of the simple regression analysis show that there is a positive and significant influence between job motivation on teacher performance as about 56.7% and multiple regression analysis shows that the leadership style variable of the principal moderates the influence between work motivation and teacher performance at SMP Negeri in Masohi City District as about 57, 9%.